Multiprocessor System-on-Chip Hardware Design and Tool Integration - Hübner, Michael; Becker, Jürgen; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Improving future electronic system performance can only be achieved by exploiting parallelism on all system levels. Multicore architectures offer a better performance/Watt ratio than single core architectures with similar performance. Combining multicore and coprocessor technology promises extreme computing power for highly CPU-time-consuming applications. FPGA-based accelerators not only offer the opportunity to speed up an application by implementing their compute-intensive kernels into hardware, but also to adapt to the dynamical behavior of an application. This book describes strategies for future system design in multiprocessor system-on-chip (MPSoC) architectures. Both hardware design and integration of new development tools are discussed. Novel trends in MPSoC design, combined with reconfigurable architectures are a main topic of concern. The main emphasis is on architectures, design-flow, tool-development, applications and system design. This book deals with key issues such as on-chip communication architectures, integration of reconfigurable hardware, and physical design of multiprocessor systems. •Provides a state-of-the-art overview of system design using MPSoC architectures; •Describes current trends in on-chip communication architectures; •Offers extensive coverage of system design integrating MPSoC architectures with reconfigurable hardware; •Includes coverage of challenges in physical design for multi- and manycore hardware architectures.
Keywords: Electronic circuits; Computer-aided engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design